Regulating the role of extended families in providing financial support under Malaysian Law - Mohd Zin, Najibah (IIUM Press, 2008)
This paper examines the adequacy of legal provisions governing the role of extended families in providing financial support under Malaysian law. This is to promote the importance of such function despite the breaking up of extended family relationships due to modernisation and urbanisation. The study focuses on Malay Muslim Family where personal law is based on Shariah and the role of extended family is an important component of the system. Besides other form of financial provisions are analysed to reflect the xtent of familial relationship in response to the current needs